Milk Phospholipids Enhance Lymphatic Absorption of Dietary Sphingomyelin in Lymph‐Cannulated Rats. Issue 10 (2nd August 2015) - Morifuji, Masashi; Higashi, Seiichiro; Oba, Chisato; Ichikawa, Satomi; Kawahata, Keiko; Yamaji, Taketo; Itoh, Hiroyuki; Manabe, Yuki; Sugawara, Tatsuya
Abstract: Supplementation with sphingomyelin has been reported to have beneficial effects on disease prevention and health maintenance. However, compared with glycerolipids, intact sphingomyelin and ceramides are poorly absorbed. Therefore, if the bioavailability of dietary sphingomyelin is increased, then the dose administered can be reduced. This study was designed to identify molecular species of ceramide in rat lymph after the ingestion of milk sphingomyelin, and to compare the effect of purified sphingomyelin with milk phospholipids concentrate (MPL, 185 mg sphingomyelin/g) on lymphatic absorption of milk sphingomyelin. Lymph was collected hourly for 6 h from lymph‐cannulated rats ( n = 8/group) after the administration of a control emulsion (triolein, bovine serum albumin, and sodium taurocholate), a sphingomyelin emulsion (control + purified sphingomyelin), or a MPL emulsion (control + MPL). Molecular species of ceramide in lymph were analyzed using high‐performance liquid chromatography‐tandem mass spectrometry (HPLC–MS/MS). Molecular species of ceramide, containing not only d 18:1, but also d 17:1 and d 16:1 sphingosine with 16:0, 22:0, 23:0, and 24:0 fatty acids (specific to milk sphingomyelin), were increased in rat lymph after the administration of milk sphingomyelin. Their molecular species were similar to those of dietary milk sphingomyelin. Recovery of ceramide moieties from dietary sphingomyelin was 1.28‐ to 1.80‐fold significantly higher in the MPL group than in the sphingomyelin group. Our results demonstrated that dietary sphingomyelin from milk was transported to lymph as molecular species of ceramide hydrolyzed from milk sphingomyelin and co‐ingestion of sphingomyelin with glycerophospholipids enhanced the bioavailability of dietary sphingomyelin.